2022
DOI: 10.1111/anae.15825
|View full text |Cite
|
Sign up to set email alerts
|

Age and the anaesthetist: considerations for the individual anaesthetist and workforce planning

Abstract: There is clear evidence of a growing workforce gap and this is compounded by demographic data that show the current workforce is ageing. Within the current workforce, more doctors are taking voluntary early retirement and the loss of these experienced clinicians from departments can have wide-ranging effects. Older doctors are at risk of age-related health problems (e.g. sight, musculoskeletal, menopause) and are more susceptible to the effects of fatigue, which may increase the risk of error and or complaint.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Concerningly, studies directly assessing specialists’ performance identified evidence of inadequate performance in managing medical emergencies and insufficient knowledge related to clinical skills and procedures. These findings corroborate existing evidence of a decline in anesthetists’ knowledge and skills over time and reinforce the importance of CPD and the need for evidence‐based educational activities that ensure safe and effective clinical practice 26 . However, they also raise multiple important ethical considerations related to the clinical implications of inadequate performance that need to be addressed within the context of CPD: should anesthetists be able to practice whilst undertaking remediating measures, should the use of assessment be increased within CPD, should there be core competencies which all anesthetists regularly recertify?…”
Section: Discussionsupporting
confidence: 83%
“…Concerningly, studies directly assessing specialists’ performance identified evidence of inadequate performance in managing medical emergencies and insufficient knowledge related to clinical skills and procedures. These findings corroborate existing evidence of a decline in anesthetists’ knowledge and skills over time and reinforce the importance of CPD and the need for evidence‐based educational activities that ensure safe and effective clinical practice 26 . However, they also raise multiple important ethical considerations related to the clinical implications of inadequate performance that need to be addressed within the context of CPD: should anesthetists be able to practice whilst undertaking remediating measures, should the use of assessment be increased within CPD, should there be core competencies which all anesthetists regularly recertify?…”
Section: Discussionsupporting
confidence: 83%
“…Davies et al stated that the successful performance of anesthesia team members relies on optimization of the ergonomics of the operating room, and if due attention is not paid to these details, their performance will be disrupted. According to their results, temperature, humidity, adequate lighting, and visibility or availability of equipment needed by the anesthesia team member in the operating room are influencing factors in this regard (34). Moreover, amenities are not equally distributed in all operating rooms.…”
Section: Discussionmentioning
confidence: 99%
“…The culture of the department should encourage formal and informal mechanisms to provide support in these circumstances. Impairment of vision and hearing tends to increase with age, and this should be recognised by the individual as well as their department [51].…”
Section: Individual/unique Considerationsmentioning
confidence: 99%